Evaluation of Recombinant Live-Attenuated Respiratory Syncytial Virus (RSV) Vaccines RSV/ΔNS2/Δ1313/I1314L and RSV/276 in RSV-Seronegative Children. (23rd June 2022) - Cunningham, Coleen K; Karron, Ruth A; Muresan, Petronella; Kelly, Matthew S; McFarland, Elizabeth J; Perlowski, Charlotte; Libous, Jennifer; Oliva, Jennifer; Jean-Philippe, Patrick; Moye, Jack; Schappell, Elizabeth; Barr, Emily; et al.
Abstract: Background: This United States-based study compared 2 candidate vaccines: RSV/ΔNS2/Δ1313/I1314L, attenuated by NS2 gene-deletion and temperature-sensitivity mutation in the polymerase gene; and RSV/276, attenuated by M2-2 deletion. Methods: RSV-seronegative children aged 6–24 months received RSV/ΔNS2/Δ1313/I1314L (10 6 plaque-forming units [PFU]), RSV/276 (10 5 PFU), or placebo intranasally. Participants were monitored for vaccine shedding, reactogenicity, and RSV serum antibodies, and followed over the subsequent RSV season. Results: Enrollment occurred September 2017 to October 2019. During 28 days postinoculation, upper respiratory illness and/or fever occurred in 64% of RSV/ΔNS2/Δ1313/I1314L, 84% of RSV/276, and 58% of placebo recipients. Symptoms were generally mild. Cough was more common in RSV/276 recipients than RSV/ΔNS2/Δ1313/I1314L (48% vs 12%; P = .012) or placebo recipients (17%; P = .084). There were no lower respiratory illness or serious adverse events. Eighty-eight and 96% of RSV/ΔNS2/Δ1313/I1314L and RSV/276 recipients were infected with vaccine (shed vaccine and/or had ≥4-fold rises in RSV antibodies). Serum RSV-neutralizing titers and anti-RSV F IgG titers increased ≥4-fold in 60% and 92% of RSV/ΔNS2/Δ1313/I1314L and RSV/276 vaccinees, respectively. Exposure to community RSV during the subsequent winter was associated with strong anamnestic RSV-antibody responses. Conclusions: Both vaccines had excellent infectivity and were well tolerated. RSV/276 induced an excess of mild cough. Both vaccines were immunogenic and primed for strong anamnestic responses. Clinical Trials Registration: NCT03227029 and NCT03422237. Abstract : Two promising live-attenuated RSV candidate vaccines, RSV/ΔNS2/Δ1313/I1314L and RSV/276, were evaluated in 65 healthy children aged 6–24 months. Both products were restricted in replication; however, RSV/276 recipients had excess cough events. RSV/ΔNS2/Δ1313/I1314L is a candidate for further clinical evaluation.